Bioerosion on late Quaternary Planktonic Foraminifera related to paleoproductivity in the western South Atlantic - Frozza, Cristiane Fraga (2020)
Planktonic Foraminifera are widely used in paleoceanographic reconstructions, although studies of their trophic interactions are still rare, especially those focusing on predation. Drilling holes are the most frequent traces of bioerosion in foraminifer tests, but environmental factors that control bioerosion are not yet understood. To determine if paleoceanographic variables are associated with bioerosion rates in late Quaternary planktonic foraminifers of the western South Atlantic, geochemical and assemblage analyses were made on a 46 kyr record from a piston core. An age model was constructed based on 10 AMS 14C dates. To reconstruct the paleoproductivity, δ13C, benthic/planktonic foraminifer and the relative abundances of Globigerina bulloides and Globigerinoides ruber (high and low productivity, respectively) were used. Bioeroded tests were counted and found in 21 of the 25 identified species, with frequencies ranging from 8.84% to 16.7%. Bioerosion was different in two groups identified by cluster analysis, with a higher intensity during glacial times, showing a strong correlation with paleoceanographic fluctuations. Paleoproductivity estimates and bioerosion rates show a significant correlation, suggesting that bioerosion is more frequent in eutrophic environments and more inhibited in oligotrophic conditions. However, even with a strong correlation between bioerosion and productivity, there is also a negative correlation with sea surface temperature in the study area. Since conditions that promote higher productivity are accompanied by a decrease in surface temperature, the precise distinction between the influence of both variables is hampered. Further research will allow us to explore the potential of planktonic foraminiferal bioerosion as a tool in paleoceanographic studies.